The Effect of World Gold Price on the Indonesia Composite Index (ICI) with Crude Oil as a Mediation Variable (2019-2023 Period) - Ardian, Bahtiar Agung; Putra, I Nyoman Nugraha Ardana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the influence of world gold prices and crude oil on the Indonesia composite index. The population used in this study is all monthly data on the closing price of world gold prices, world oil prices, and the Indonesia Composite Index for the 2019-2023 Period, which is as much as 60 data taken based on monthly data. This data was analyzed using regression analysis methods and the Sobel test. Empirical results show that world gold and crude oil prices positively influence the Indonesia Composite Index. Meanwhile, the world gold price does not affect the price of crude oil, and the price of crude oil does not mediate the influence of the world gold price on the Composite Stock Price Index.